A short biography of Olympian Leszek Bebło - Bartłomiej Tworek (University of Applied Sciences in Tarnow, Poland, 2023)
Sport is one of the forms of participation in physical culture. Marathon runner Leszek Bebło is an example of participation in physical culture through sport. The track and field athlete has left his mark on the history of Polish athletics through his participation in two Olympic Games, the World Championships in Stuttgart, and as a winner of many prestigious foreign races, including being the only Pole to win the Paris Marathon, which has been held since 1896.